Associated Clinical Disorders Diagnosed by Medical Specialists in 188 FMR1 Premutation Carriers Found in the Last 25 Years in the Spanish Basque Country: A Retrospective Study - Merino, Sonia (Genes (Basel), 2016)
Fragile X-associated tremor/ataxia syndrome (FXTAS) and fragile X-associated primary ovarian insufficiency (FXPOI) are definitely related to the fragile X mental retardation 1 (FMR1) premutation (PM). Additional medical problems have also been associated with the PM, such as fibromyalgia, endocrine, and psychiatric disorders. To improve our understanding in the field, we reviewed all PM carriers and their reasons for any medical referrals from 104 fragile X families molecularly diagnosed in our laboratory and living in the Spanish Basque Country. After signing the written informed consent, we studied their electronic medical records in order to identify the disorders associated with the PM and their frequencies. We obtained clinical data in 188 PM carriers (147 women and 41 men). In women, the frequency of FXPOI (22.61%) was similar to that previously reported in PM carriers. In men, the frequency of definite FXTAS (28.57%) was lower than reported elsewhere. Furthermore, thyroid pathology was associated with the PM, the frequency of hypothyroidism being much higher in the studied region than in the general population (8.84% vs. 0.93%). Finally, we found no association with fibromyalgia or psychiatric problems. These findings represent another population contribution in this field and may be useful for the clinical management of PM carriers.